The digital twin: New opportunities for diagnostics and control? - Wahl, P.; Broich, H. (Sports technology. Fields of application, sports equipment and materials for sport, 2024)
Personalized training requires the integration and processing of large amounts of data. One solution to this challenge could be the construction of digital twins. Digital twin technology has gained popularity in the last decade thanks to the popularity of machine learning. The chapter highlights the prerequisites and techniques such an approach requires and the challenges of developing a decision support system or a digital twin coaching approach.